ANALISIS KESANTUNAN BERBAHASA DALAM ACARA KUNCUNG BAWUK TVRI JOGJA - Lia Kurnia; Kenfitria Diah Wijayanti; Favorita Kurwidaria (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2020)
This research aims to describe and explain the form of language politeness in the program Kuncung Bawuk TVRI Jogja. This research is a qualitative descriptive study. The approach used is a pragmatic approach. The data in this study are utterances containing language politeness, while the source of data in this study is the transcript of the dialogue in the program Kuncung Bawuk. The data collection technique was carried out by the listening method and the speaking method. The sampling technique used in this research is purposive sampling or certain considerations. The data validity test technique in this study used theoretical triangulation. The data analysis technique used in this research is content analysis technique. Based on the results of the research that has been done, the speech in the program Kuncung Bawuk TVRI Jogja, found the form of politeness in Javanese language as many as 23 data including: (a) the maxim of kurmat/respect as many as 10 data; (b) maxim andhap asor/humble as many as 3 data; (c) the maxim of empan papan/awareness of place as many as 6 data; and (d) the maxim of tepa slira/tolerance of 4 data.